Recalling the Biological Significance of Immune Checkpoints on NK Cells: A Chance to Overcome LAG3, PD1, and CTLA4 Inhibitory Pathways by Adoptive NK Cell Transfer? - Lanuza, Pilar M.; Pesini, Cecilia; Arias, Maykel A.; Calvo, Carlota; Ramirez-Labrada, Ariel; Pardo, Julian (Frontiers in Immunology, 2020)
Immune checkpoint receptors (IC) positively or negatively regulate the activation of the host immune response, preventing unwanted reactions against self-healthy tissues. In recent years the term IC has been mainly used for the inhibitory ICs, which are critical to control Natural Killer (NK) and Cytotoxic CD8+ T cells due to its high cytotoxic potential. Due to the different nature of the signals that regulate T and NK cell activation, specific ICs have been described that mainly regulate either NK cell or T cell activity. Thus, strategies to modulate NK cell activity are raising as promising tools to treat tumors that do not respond to T cell-based immunotherapies. NK cell activation is mainly regulated by ICs and receptors from the KIR, NKG2 and NCRs families and the contribution of T cell-related ICs is less clear. Recently, NK cells have emerged as contributors to the effect of inhibitors of T cell-related ICs like CTLA4, LAG3 or the PD1/PD-L1 axes in cancer patients, suggesting that these ICs also regulate the activity of NK cells under pathological conditions. Strikingly, in contrast to NK cells from cancer patients, the level of expression of these ICs is low on most subsets of freshly isolated and in vitro activated NK cells from healthy patients, suggesting that they do not control NK cell tolerance and thus, do not act as conventional ICs under non-pathological conditions. The low level of expression of T cell-related ICs in “healthy” NK cells suggest that they should not be restricted to the detrimental effects of these inhibitory mechanisms in the cancer microenvironment. After a brief introduction of the regulatory mechanisms that control NK cell anti-tumoral activity and the conventional ICs controlling NK cell tolerance, we will critically discuss the potential role of T cell-related ICs in the control of NK cell activity under both physiological and pathological (cancer) conditions. This discussion will allow to comprehensively describe the chances and potential limitations of using allogeneic NK cells isolated from a healthy environment to overcome immune subversion by T cell-related ICs and to improve the efficacy of IC inhibitors (ICIs) in a safer way.